Sistem Penyiraman Tanaman Otomatis Berbasis Arduino - YR, Kenny Philander; Suppa, Rinto; Muhallim, Muhlis (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2021)
This study aims to create an Arduino-based automatic plant watering system, in which the water pump can pump water automatically based on the reading from the soil moisture sensor, which aims to make it easier for people to water plants. This research was conducted at the Palopo City Agriculture Office. The results of this study indicate that users no longer need to water plants manually. In designing an Arduino-based Automatic Plant Watering System, a microcontroller and several components are used, including: Arduino UNO, FC-28 moisture sensor, water pump, relay, 16x2 LCD and breadboard. This tool works by reading data from the soil moisture sensor, if The sensor detects dry soil levels, then the data from the sensor will be read by Arduino. The data that has been read by Arduino will be forwarded to the relay, then the relay will forward the data that will be used to turn on or turn off the water pump